Visceral Adiposity Index and Insulin Resistance in Diabetes Mellitus Type 2 - Hendrianingtyas, Meita; Pradati, Subandhini Arika (Journal of Biomedicine and Translational Research, 2024)
Background: Diabetes mellitus (DM) has been increasing worldwide. Obesity, especially central obesity, is a sign of increased visceral fat in various diseases, especially DM. Individuals with visceral fat compromise insulin resistance and metabolic disorders and develop diabetes. The gold standard for assessing insulin resistance is the hyperinsulinemic-euglycemic clamp (HEC). However, this method is invasive and expensive, so the homeostasis model assessment-insulin resistance (HOMA-IR) and the quantitative insulin sensitivity check index (QUICKI) are more straightforward, more practical, and invasive measurement methods. Visceral adiposity index (VAI) was developed as a new indicator of visceral adipose tissue dysfunction that can be used for CT examination as a marker of visceral adiposity.Objective: To determine the correlation between visceral adiposity index and insulin resistance in patients with type 2 diabetes mellitusMethods: The study was conducted as an analytical observational study using a cross-sectional design approach at the Diponegoro National Hospital Semarang from March to April 2022. Data analysis using the Pearson test (meaningful if p < 0.05)Results: From the 70 samples examined, there was a correlation between VAI and HOMA-IR (r=0,480; p=<0,001), VAI and QUICKI (r=-0,475; p=<0,001), and a strong correlation between HOMA-IR and QUICKI (r=-0,892; p=<0,001)Conclusion: There was a moderate positive correlation between VAI and HOMA-IR and a moderate negative correlation between VAI and QUICKI. Meanwhile, the results of the correlation test between HOMA-IR and QUICKI show that there is a robust negative correlation.